The Significance of CK18 and Azonulin when Evaluating Nonalcoholic Fatty Liver Diseases in the Iraqi Community - Murtadha, Nawal Abdullah (Central Asian Journal of Medical and Natural Science, 2025)
Nonalcoholic fatty liver disease (NAFLD), which impacts over twenty-five percent of the worldwide population, has emerged as an important issue for the public. This prevalent liver disease is characterized by excess fat buildup after hepatic steatosis, with or without hepatocyte loss, various types of inflammatory cells infiltration, nonalcoholic steatohepatitis, and, in rare instances, cirrhosis and cancer of the liver. Cytokeratin 18 (CK18), which is a marker of apoptosis and overall cell death, is an excellent biomarker for NAFLD. Liver fat accumulation in NAFLD triggers the activation of caspases, which increases the CK18 cleavage and its release into the blood. CK18 can help diagnose different stages of NAFLD, especially the nonalcoholic steatohepatitis (NASH) stage. CK18 is important for assessing the success of NAFLD treatment and forecasting the risk of NAFLD-related illnesses. The zonulin test can detect intestinal permeability among individuals with nonalcoholic fatty liver disease (NAFLD), which is typically elevated.